Chaos and complexity in financial statements (2015)
Conceptual issues and the basis for the use of financial statements from the perspective of complexity and chaos are proposed. After analyzing the implications that these perspectives have for financial statements, basic accounting equation is examined from the view of complex logic through the mechanisms of the circumscription. Besides, the phase spaces arising from the relationship between indicators of financial health, such as total assets, stakeholder's equity, profit and loss, or cash flow at end of year, are analyzed; also, the relationship among ratios of sustainability, liquidity, and profitability is revisited. The management discussion and analysis and notes to financial statements sections of financial statements are subjected to new interpretations, based on the beliefs logic and complex and chaotic metaphorical narratives. Finally, a critical perspective on the use of chaos and complexity in the analysis of financial statements is introduced. © 2015, IGI Global. All rights reserved.